Liquid ionization chambers for LET determination - Kaiser, Franz-Joachim; Bassler, Niels; Tölli, Heikki; Jäkel, Oliver (Radiation measurements, 2010)
Modern radiotherapy facilities for cancer treatment such as the Heavy Ion Therapy Centre (HIT) in Heidelberg (Germany) enable sub millimetre precision in dose deposition. For the measurement of such dose distributions and characterization of the particle beams, detectors with high spatial resolution and high sensitivity are necessary. For exact dosimetry which is done using ionization chambers (ICs), the recombination taking place in the IC has to be known. Up to now, recombination is corrected phenomenologically and more practical approaches are currently used. Nevertheless, Jaffés theory of columnar recombination was designed to model the detector efficiency of an ionization chamber. Here, we have shown that despite the approximations and simplification made, the theory is correct for the LETs typically found in clinical radiotherapy employing particles from protons to carbon ions. As no exact closed solution is available, a numerical solver was programmed.
Gesehen am 28.02.2023